Produce Basket: The Effect of Experiential Fraction Pedagogy on Preservice Teacher Learning - Adams, Deb; Bucci, Terri; McEwan, Lee; Reinthal, Kevin (Ohio Journal of School Mathematics, 2022)
Formal notation of fractions is a critical stumbling block for students, impeding their progress to acquire flexible number sense beyond integers and greatly impacting their success in algebra. Conflicting and vague definitions of fractions are a major cause of confusion and frustration among students and their teachers. A team consisting of a veteran fourth-grade teacher, a professional development leader/university instructor, a math educator, and a mathematician developed an experiential learning module called Produce Basket (PB) for elementary grades fraction learning. Since its inception 5 years ago, PB has been taught in about a dozen elementary classrooms in north central Ohio and is woven into the preservice teaching program at Ohio State University Mansfield. Given the high stakes and strong claims for this approach, there is now a pressing need to assess the strengths and weaknesses of Produce Basket’s approach. The aim of this article is to report research conducted with two classes (total n = 22) of preservice teachers that were instructed over an 8-week period with PB. The study finds initial evidence that PB improves student understanding of fractions. The authors used both quantitative and qualitative instruments to measure student understanding.